Immunoliposomes. - SENGE, MATHIAS (My University, 2012)
Since their discovery by Bangham about 50 years ago, liposomes have become promising tools in drug delivery systems. This has increased the therapeutic index of many drugs, and offers improved drug targeting and controlled release. In order to further improve the specificity of liposomes for malignant tissues, targeted liposomal formulations have been developed which represent the next step of liposomal drug delivery in medical treatment. Antibodies and antibody fragments are the most widely used targeting moieties for liposomes due to the high specificity for their target antigens. This has given rise to a new class of drug delivery vehicles, the so-called immunoliposomes. Immunoliposomes are generated by coupling of antibodies to the liposomal surface and allow for an active tissue targeting through binding to tumor cell-specific receptors. Such antibody modified liposomes are attracting great interest for their potential use in specific drug delivery to cancer cells, gene therapy, drug delivery through blood brain barrier, or molecular imaging. Thus far, immunoliposomes show promising results in vitro and in vivo and appear to be effective systems for improvements in cancer treatment. This review covers the literature of the past decade with special emphasis on in vitro and in vivo studies.
PUBLISHED
Keywords: Liposomes